Guidelines for engineering design for process safety. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1993)
Inherently safer plants begin with the initial design. Here is where integrity and reliability can be built in at the lowest cost, and with maximum effectiveness. This book focuses on process safety issues in the design of chemical, petrochemical, and hydrocarbon processing facilities. It discusses how to select designs that can prevent or mitigate the release of flammable or toxic materials, which could lead to a fire, explosion, or environmental damage. All engineers on the design team, the process hazard analysis team, and those who make basic decisions on plant design, will benefit from it.